Experimental response of cold-formed steel lipped channel beam-columns. (April 2015) - Torabian, Shahabeddin; Zheng, Baofeng; Schafer, Benjamin W.
Abstract: In this paper, the structural strength and stability of cold-formed steel lipped channel beam-columns under bi-axial moments and axial force are experimentally investigated. The results are employed to evaluate the reliability of the current North American cold-formed steel design standard, AISI-S100-12, for predicting the strength of beam-columns, by both the effective width method (EWM) and the direct strength method (DSM). Fifty-five 600S137-54 (AISI-S200-12 nomenclature) lipped channel beam-column sections with three different lengths: 305 mm (short), 610 mm (intermediate), and 1219 mm (long) are tested under combined bi-axial bending moments and axial force to characterize the failure modes and the member capacity. A loading rig specifically designed to apply eccentric axial load, in order to provide bi-axial bending and compression to the specimens, was developed and detailed herein. The experimental observations reveal that the failure modes are highly dependent on the stress distribution applied on the cross-section by the combined actions. The results show a considerable potential for improvement in current specification approaches which utilize a simple interaction equation, as this typically results in conservative strength predictions. The potential for further improvement of the current specification for predicting the strength of cold-formed steel beam-columns is discussed. Graphical abstract: Highlights: Design codes do not consider actual stress distribution in the design of beam-columns. Fifty-five lipped channel beam-columns were tested to evaluate AISI-S100-12. A special loading rig was used to apply eccentric axial loads to the specimens. Stress distributions is modulating the failure mechanisms. Ductility is correlated to the degree of eccentricity in the axial load. Both EWM and DSM are conservative due to a linear interaction expression.